Long-wave infrared photothermoelectric detectors with ultrahigh polarization sensitivity - Dai, Mingjin (2023)
Filter-free miniaturized polarization-sensitive photodetectors have important applications in the next-generation on-chip polarimeters. However, their polarization sensitivity is thus far limited by the intrinsic low diattenuation and inefficient photon-to-electron conversion. Here, we implement experimentally a miniaturized detector based on one-dimensional tellurium nanoribbon, which can significantly improve the photothermoelectric responses by translating the polarization-sensitive absorption into a large temperature gradient together with the finite-size effect of a perfect plasmonic absorber. Our devices exhibit a zero-bias responsivity of 410 V/W and an ultrahigh polarization ratio (2.5 × 104), as well as a peak polarization angle sensitivity of 7.10 V/W•degree, which is one order of magnitude higher than those reported in the literature. Full linear polarimetry detection is also achieved with the proposed device in a simple geometrical configuration. Polarization-coded communication and optical strain measurement are demonstrated showing the great potential of the proposed devices. Our work presents a feasible solution for miniaturized room-temperature infrared photodetectors with ultrahigh polarization sensitivity.